(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2014)
Drawing on philosophy and psychoanalysis, this paper explores the essential nature of love. It investigates the significance of productive destruction for our capacity to love, highlights the affinities between the baby’s earliest object-relation and the ethical relationship in Levinas’ philosophy, and questions Levinas’ eagerness to purge ethics of eroticism.